PENGARUH PENERAPAN FOUR PILLARS APPROACH TERHADAP KEPATUHAN IBU HAMIL DALAM MELAKUKAN ANTENATAL CARE (ANC) - Dinda Pramestya Utami; Nina Herlina (JHN: Journal of Health and Nursing, 2026)
Adherence to antenatal care (ANC) visits among pregnant women is crucial for the early detection of pregnancy risks and the improvement of maternal and fetal health. However, non-adherence to ANC visit schedules remains a frequently encountered issue. The Four Pillars Approach is a comprehensive strategy encompassing healthy lifestyle habits during pregnancy, family social support, healthcare worker competence, and the professional behavior of healthcare workers. This study aimed to analyze the impact of implementing the Four Pillars Approach on ANC visit adherence among pregnant women at the Cogreg Community Health Center (Puskesmas), Bogor Regency, in 2025. A quantitative method with a cross-sectional design was employed. The study sample consisted of 56 third-trimester pregnant women selected via purposive sampling. Data analysis was conducted using the chi-square test. The results indicated that a healthy lifestyle during pregnancy had a significant influence on ANC adherence (p = 0.029). Meanwhile, family social support, healthcare worker competence, and professional behavior among healthcare workers did not show a statistically significant influence (p > 0.05), although they remained supporting factors. The study concludes that a healthy lifestyle during pregnancy is the dominant factor influencing ANC adherence. This study also discusses practical implications, strengths, and limitations, serving as a basis for recommendations regarding maternal health services and future research.